**Answer:**

the three consecutive even integers are **-2, 0, 2**

**Step-by-step explanation:**

Let the first even integer = n

Let the second even integer = n + 2

Let the third even integer = n + 4

From the given statement, we form the equation below

(n²) + (n + 2)² + 4 = 2(n + 4)²

Expand this equation;

n² + (n + 2)(n + 2) + 4 = 2(n + 4)(n + 4)

n² + n² + 2n + 2n + 4 + 4 = 2(n² + 4n + 4n + 16)

2n² + 4n + 8 = 2(n² + 8n + 16)

2n² + 4n + 8 = 2n² + 16n + 32

collect like terms together;

2n² - 2n² + 4n - 16n = 32 - 8

- 12n = 24

-n = 24/12

-n = 2

n = -2

Second integer = n + 2

= -2 + 2 = 0

Third integer = n + 4

= -2 + 4

= 2

Therefore, the three consecutive even integers are **-2, 0, 2**